2006
DOI: 10.1007/s10659-005-9039-8
|View full text |Cite
|
Sign up to set email alerts
|

Some Basis-Free Formulae for the Time Rate and Conjugate Stress of Logarithmic Strain Tensor

Abstract: In this paper, two kinds of tensor equations are studied and their solutions are derived in general cases. Then, some compact basis-free representations for the time rate and conjugate stress of logarithmic strain tensors are proposed using six different methods. In addition, relations between the coefficients in these expressions are disclosed. Subsequently, all these basis-free expressions given in this paper are validated for the cases of distinct stretches and double coalescence, respectively. (2000): 74b2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…According to meso-mechanics it has been revealed that failure of structure plane is affected not only by the mechanical property of filling in plane but also by the geometry, microscopic structure as well as the filling percentage [78,79]. Dui et al [80][81][82][83] developed the basic theory of meso-mechanics. They obtained an explicit theoretical solution of Eshelby tensor for transversely isotropic inclusion; and proposed the meso-mechanics model of multiple medium for analyzing fractured layer rock; established several non-linear constitutive models ( Figure 5) for structure plane, which can reflect the post-peak softening due to wear of ledges on the plane, the coupling in normal and tangential directions, and the effect of the filling material.…”
Section: The Damage Mechanism Of Dam Concrete and Foundation Rockmentioning
confidence: 99%
“…According to meso-mechanics it has been revealed that failure of structure plane is affected not only by the mechanical property of filling in plane but also by the geometry, microscopic structure as well as the filling percentage [78,79]. Dui et al [80][81][82][83] developed the basic theory of meso-mechanics. They obtained an explicit theoretical solution of Eshelby tensor for transversely isotropic inclusion; and proposed the meso-mechanics model of multiple medium for analyzing fractured layer rock; established several non-linear constitutive models ( Figure 5) for structure plane, which can reflect the post-peak softening due to wear of ledges on the plane, the coupling in normal and tangential directions, and the effect of the filling material.…”
Section: The Damage Mechanism Of Dam Concrete and Foundation Rockmentioning
confidence: 99%
“…for the unknown X in terms of Y which is either symmetric or skew, and X is of the opposite parity [5]. The equation can be written …”
Section: Application To Strain Measure Functionsmentioning
confidence: 99%
“…The first term on the right-hand side of (97) is the coaxial part of (e (2) ) J with V in the case of distinct principal stretches. The other terms are orthogonal to V.…”
Section: Basis-free Expression In the Case Of Distinct Principal Strementioning
confidence: 99%
“…Hence, some authors have been attracted to derive expressions for them during the past decades. In the context of providing expressions for the material time derivative or material time rate of kinematic tensors, specially the material time rate of strain measures, the works of Hill [10,11], Gurtin and Spear [5], Guo [6], Guo and Dubey [7], Hoger and Carlson [13], Hoger [12], Mehrabadi and Nemat-Nasser [17], Guo et al [8], Scheidler [23,24], Wang and Duan [26], Man and Guo [16], Naghdabadi et al [19], Xiao [27,29] and Dui et al [2,3] can be mentioned.…”
mentioning
confidence: 99%